2005
DOI: 10.1358/dot.2005.41.1.875777
|View full text |Cite
|
Sign up to set email alerts
|

The causes of skin cancer: A comprehensive review

Abstract: Skin cancer is the most common type of cancer in fair-skinned populations around the world. The incidence and mortality rates of skin cancers are dramatically increasing and thus pose a threat to public health. Understanding the etiology and pathogenesis of skin cancer remains a goal for healthcare systems. A clearer understanding of causative factors is an essential step in the prevention of skin cancer. This article comprehensively reviews the causative agents which play a role in the development of skin can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(101 citation statements)
references
References 0 publications
1
93
0
7
Order By: Relevance
“…The link between chronic inflammation from sun exposure and skin cancer development has been established in both humans (70)(71)(72) and animal models (27,73). Chronic inflammation is believed to promote genetic changes, tumor angiogenesis, tumor progression and metastasis (reviewed in (32,33,74)).…”
Section: Duncan Et Almentioning
confidence: 99%
“…The link between chronic inflammation from sun exposure and skin cancer development has been established in both humans (70)(71)(72) and animal models (27,73). Chronic inflammation is believed to promote genetic changes, tumor angiogenesis, tumor progression and metastasis (reviewed in (32,33,74)).…”
Section: Duncan Et Almentioning
confidence: 99%
“…Therefore the study of the conversion pathways of the substantial energy deposited by light absorption is of great importance. [1][2][3][4] The excited ππ* states of these complex aromatic systems mostly undergo non-radiative relaxation, namely either internal conversion or intersystem crossing to other dark or weakly allowed states, which could initiate photochemical processes. It is often stated that these latter processes are made highly improbable by a very fast (picosecond) internal conversion to the electronic ground state where the electronic energy is eventually thermalised, providing nucleobases with a high level of photostability.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers showed that ultraviolet radiation (UVR) from the solar would be a principal cause of skin melanoma [13,14]. The bigger the UPF worth, the longer a person can stay within the sun until the area of epidermis underneath the material turns into red.…”
Section: Uv-protectionmentioning
confidence: 99%